Agronomic Traits and Molecular Marker Identification of Wheat–Aegilops caudata Addition Lines - Gong, Wenping; Han, Ran; Li, Haosheng; Song, Jianmin; Yan, Hongfei; Li, Genying; Liu, Aifeng; Cao, Xinyou; Guo, Jun; Zhai, Shengnan; Cheng, Dungong; Zhao, Zhendong; et al. (Frontiers in Plant Science, 2017)
Aegilops caudata is an important gene source for wheat breeding. Intensive evaluateion of its utilization value is an essential first step prior to its application in breeding. In this research, the agronomical and quality traits of AlcedoTriticum aestivum-Ae. caudata additions B-G (homoeologous groups not identified) were analyzed and evaluated. Disease resistance tests showed that chromosome D of Ae. caudata might possess leaf rust resistance, and chromosome E might carry stem rust and powdery mildew resistance genes. Investigations into agronomical traits suggested that the introduction of the Ae. caudata chromosome in addition line C could increase thousand-kernel weight, chromosomes E and F could reduce plant height, while chromosome G could increase wheat leaf length and spikelet number. Grain quality tests showed that the introduction of chromosomes E or F into wheat could increase its protein and wet gluten content. Therefore, wheat-Ae. caudata additions C-GF are all potentially useful candidates for chromosome engineering activities to create useful wheat-alien chromosome introgressions. A total of 55 EST-based molecular markers were developed and then used to identify the chromosome homoeologous group of each of the Ae. caudata B-G chromosomes. Marker analysis indicated that the Ae. caudata chromosomes in addition lines B to G were structurally altered, therefore, a large population combined with intensive screening pressure should be taken into consideration when inducing and screening for wheat-Ae. caudata compensating translocations. Marker data also indicated that the Ae. caudata chromosomes in addition lines C-F were 5C, 6C, 7C and 3C, respectively, while the homoeologous group of chromosomes B and G of Ae. caudata are as yet undetermined and need further research.